Whence the Lesbian in Queer Monumentality? Intersections of Gender and Sexuality in Public Memory. Issue 4 (8th August 2017) - Dunn, Thomas R.
ABSTRACT: This article considers issues of lesbian representation within what I call "queer monumentality, " particularly the installation of LGBTQ monuments, memorials, and statuary. More specifically, the article raises awareness of gender exclusions within queer monuments and identifies two kinds of factors that contribute to this inequity. First, lesbians go underrepresented within this memory form because they are women—a group rarely afforded opportunities to do acts traditionally considered worthy of remembrance or whom only appear in monuments allegorically. Second, lesbians are also excluded from queer monuments due to particular gendered experiences within LGBTQ life, particularly separatism, HIV/AIDS, and representational reimaginings. I conclude by articulating the unique memory issues at work when sexuality and gender are viewed intersectionally.